PRINCIPAL COMPONENT AND DISCRIMINANT ANALYSES OF BODY WEIGHT AND CONFORMATION TRAITS OF SASSO, KUROILER AND INDIGENOUS FULANI CHICKENS IN NIGERIA - A. Yakubu; M. M. Ari (Journal of Animal and Plant Sciences, 2018)
This study aimed at evaluating the body weight (BW) and biometric traits [breast girth (BG), neck circumference (NC), Back length (BL), wing length (WL), thigh length (TL), thigh circumference (TC), shank length (SL) and shank circumference (SC)] of two newly introduced and one Nigerian indigenous chicken strains using multivariate principal components (PCs) and to classify the three genotypes using discriminant analysis. A total of one hundred and fifty chickens of both sexes comprising equal number of Sasso, Kuroiler and the local Fulani ecotype were utilized in the study. The six-week old birds were managed intensively in a private farm in Nasarawa State, north central Nigeria. The fixed genotype and sex effects including their interaction on the body parameters were tested using general linear model. With the exception of BG, the univariate analysis showed that Kuroiler birds had higher (P<0.05) BW and morphometric traits than Sasso, which in turn, were superior (P<0.05) to their Fulani counterparts. Male chickens also exhibited better performance (P<0.05) than their female counterparts. There was genotype * sex interaction effect on all the body traits, except TC. The phenotypic correlations among the traits were positive and significant (P<0.05; P<0.01) ranging from 0.41-0.97, 0.47-0.96 and 0.42-0.94 in Sasso, Kuroiler and Fulani chickens, respectively. Factor analysis with varimax rotation of interrelated traits revealed three PCs (Sasso and Kuroiler) and two PCs (Fulani) which accounted for 87.4, 93.9 and 78.9% of the total variance in the genetic groups. The PC-based regression models, which are preferable for selecting birds for optimal balance, accounted for 92, 95 and 88% of the total variation in the BW of Sasso, Kuroiler and Fulani chickens, respectively. The chicken genotypes were best separated using BG, SC, BW and TC.
Keywords: body traits; chickens; genetic groups; Multivariate; Nigeria